Soil Phosphorus Availability Modulates Host Selectivity of Pedicularis kansuensis Between Legumes and Grasses - Xiaolin Sui; Ruijuan Xue; Airong Li (Plants)
Host selectivity or preference plays a critical role in enabling parasitic plants to identify suitable hosts and influence plant community dynamics. Phosphorus (P) is known to affect the growth of root hemiparasitic plants and their interaction with single host species, but its role in shaping host selectivity across multiple hosts is unclear. In a pot experiment, we used a grass–legume co-culture design and evaluated whether the root hemiparasitic plant Pedicularis kansuensis exhibits selective parasitism on legumes (Medicago sativa) versus grasses (Elymus nutans) and assessed the impact of soil P availability on this preference. The results showed that P. kansuensis inhibited the growth of both host species, but the magnitude of suppression varied with P availability. Under low P conditions, P. kansuensis preferentially parasitized the tender M. sativa, causing a greater biomass reduction in the legume. In contrast, at high P levels, P. kansuensis decreased its foraging on legumes, shifting its parasitism towards the dominant E. nutans, which potentially led to stronger suppression of grass growth. Our findings demonstrate that soil P availability modulates host selectivity in P. kansuensis, emphasizing the influence of soil nutrient conditions on parasite–host dynamics. This research provides insights into managing the impacts of parasitic plants on plant community structure through nutrient interventions.